2019
DOI: 10.3390/en12203909
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of End-Gas Autoignition and Pressure Oscillation in a Downsized SI Engine Using Large Eddy Simulation

Abstract: Knock and super-knock are abnormal combustion phenomena in engines, however, they are hard to study comprehensively through optical experimental methods due to their inherent destructive nature. In present work, the methodology of large eddy simulation (LES) coupled with G equations and a detailed mechanism of primary reference fuel (PRF) combustion is utilized to address the mechanisms of knock and super-knock phenomena in a downsized spark ignition gasoline engine. The knock and super-knock with pressure osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A few studies have attempted to examine how turbulence affects the intensity of the developing detonation. Wei et al (2016), Chen et al (2019 and Zhong and Liu (2019) used reduced-order turbulent models and found that increased turbulence intensity inhibits autoignition formation and reduced hot spot sizes, leading to different autoignition modes and knock intensities. Zhang et al (2019) studied the interaction of turbulent transport and low-temperature chemistry on knocking formation of an imposed hot spot.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have attempted to examine how turbulence affects the intensity of the developing detonation. Wei et al (2016), Chen et al (2019 and Zhong and Liu (2019) used reduced-order turbulent models and found that increased turbulence intensity inhibits autoignition formation and reduced hot spot sizes, leading to different autoignition modes and knock intensities. Zhang et al (2019) studied the interaction of turbulent transport and low-temperature chemistry on knocking formation of an imposed hot spot.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works [34][35][36], we have comprehensively validated the present models in terms of pressure profiles and heat release rate. The numerical pressure evolution agrees well with the experimental results, both in ST-10 case and ST-18 cases.…”
Section: Model Validationmentioning
confidence: 88%
“…The detailed numerical models can be found in Ref. [34][35][36]. The geometry model, which consists of a combustion chamber, an inlet port, and an outlet port, together with its grid splitting, can be found in Figure 2.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Detonation should occur in the combustion chamber, which could cause serious damage to the piston. Compressed by the piston, the mixture rapidly reached a state of high temperature and high pressure [21]. Spontaneous ignition occurred at the TDC and, subsequently, the pressure profile deviated from the normal combustion, and jumped to the Pmax value.…”
Section: Super-knock In Misfired Cylindermentioning
confidence: 99%